Penerapan YOLO Untuk Identifikasi Dan Penayangan Informasi Peralatan Laboratorium Dalam Mendukung Merdeka Belajar - Arief, Lathifah; Muhammad, Fauzan (The Indonesian Journal of Computer Science, 2022)
Computer Laboratory serves as the place to conduct experimentation in regards to Computer System. During the practical or experimentation, it is not rare to see the confusion or misunderstanding of what to do or what is needed. This problem comes from lack of knowledge and how one or more dsvice is identical to another. With the development of technology, the new method using machine learning is made for soving these problems. The system with You Only Look Once method will detect the device on camera, and then showing the file that contains datasheet explaining what that device is and how to use it. This system can also be used at anytime so everyone can learn through it and improves the efficieny of the study.